The impact of gender on financial performance: Evidence from a sample of Portuguese SMEs - Maldonado, Isabel (2020)
The objective of the present paper is to study the effects of gender on financial performance and examine the variables that may influence the presence of women leading the firm or being its main shareholder. The relation between gender and profitability in the context of Small and Medium Enterprises (SMEs) is a less studied topic in the broader context of performance determinants. Contributing to fill this research gap, it is used an unbalanced panel data of 141 Portuguese firms for the period from 2010 to 2018, obtained with primary and secondary data sources. The relation between gender and financial performance is addressed with two methodologies, a Tobit regression and a Random Effects Model. Our results evidence fewer possibilities for women to be firm leaders in larger and older organizational structures, which do not seem pressured towards equality. Additionally, firm age moderates the positive relation between female leadership and profitability. Given the SMEs importance in the majority of countries, the results and implications of this paper can be generalized to other economies.